A Family of Enhanced Voltage Gain Switched-Boost Impedance-Source Inverter Topologies for Renewable Energy Resources - Ahmad A.; Singh R.K.; Nandan Lal V. (My University, 2025)
In this paper switched-inductor and switchedcapacitor concept is used in order to obtain higher voltage gain with very low duty ratio. The classical Z-source inverters (ZSIs) gives low voltage gain and to achieve higher gain it needs to operate at a high duty cycle, and therefore, modulation index decreases which degrade the quality of output voltage. The switched-inductor-capacitor concept is applied to the classical ZSI, discontinuous input current quasi-ZSI (qZSI) and continuous input current qZSI and three different versions of each are proposed in the paper. In this way, nine enhanced switched-inductor-capacitor based ZSI topologies are proposed. The proposed topologies give higher voltage gain with very low duty ratio as compared to the existing switched inductor qZSIs and therefore, can operate at the higher value of M to improve the quality of output voltage. Detailed experimental results are presented to validate the performance of proposed inverter topologies. © 2019 IEEE.